2013
DOI: 10.1021/ef401145w
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Production from High Temperature Pyrolysis/Steam Reforming of Waste Biomass: Rice Husk, Sugar Cane Bagasse, and Wheat Straw

Abstract: Hydrogen production from pyrolysis, steam reforming, and catalytic steam reforming of sugar cane bagasse, wheat straw, and rice husk were investigated using a two stage pyrolysis-reforming system. Biomass samples were pyrolyzed in the first stage, and the volatiles and liquids were reformed in the second stage in the presence of steam. During all experiments, a high temperature of 950 °C was chosen for both the pyrolysis and reforming stages. As compared to low temperatures, pyrolysis/reforming carried out at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 93 publications
(46 citation statements)
references
References 71 publications
0
44
2
Order By: Relevance
“…However, it can be inferred that the unit cost for production of syngas from biomass pyrolysis/reforming was higher than from solid biomass gasification because the former was technically more complex than the latter. Based on a study by Wright et al, (2008) a plant of 4.04 Â 10 7 gge/a capacity (the optimal size) could produce Fischer-Tropsch liquids from solid biomass gasification to Fischer-Tropsch diesel at a unit cost of $1.77/gge (Waheed and Williams, 2013). Therefore, bio-oil gasification may be commercially more attractive than biomass pyrolysis/reforming.…”
Section: A Comparison Between Bio-oil Gasification and Biomass Pyrolymentioning
confidence: 99%
“…However, it can be inferred that the unit cost for production of syngas from biomass pyrolysis/reforming was higher than from solid biomass gasification because the former was technically more complex than the latter. Based on a study by Wright et al, (2008) a plant of 4.04 Â 10 7 gge/a capacity (the optimal size) could produce Fischer-Tropsch liquids from solid biomass gasification to Fischer-Tropsch diesel at a unit cost of $1.77/gge (Waheed and Williams, 2013). Therefore, bio-oil gasification may be commercially more attractive than biomass pyrolysis/reforming.…”
Section: A Comparison Between Bio-oil Gasification and Biomass Pyrolymentioning
confidence: 99%
“…However, hydrogen production from fossil fuels is considered unsustainable and alternative, more carbon-neutral sources for hydrogen production are under consideration [3]. Hydrogen may be produced from biomass via gasification/reforming processes [4][5][6][7]. The process of biomass gasification/reforming is still developing and there are challenges related to the upgrading and cleaning of the product synthesis gas.…”
Section: Introductionmentioning
confidence: 99%
“…In our previous work, we used a two-stage pyrolysis-catalytic reforming reactor system to compare the H2 yield from rice husks, sugarcane bagasse and wheat straw in the presence of dolomite and Ni-dolomite catalysts [6]. The second stage catalytic reforming was carried out at 950 °C and the results showed that H2 production was increased in the presence of the Ni-dolomite.…”
Section: Introductionmentioning
confidence: 99%
“…22 Hydrogen production occurs at a high temperature (>600 ∘ C), and it is therefore related to the fourth peak. 30 Comparing the two behaviors shown in Fig. 3(A) and 3(B), it can be observed that the area of the first peak is lower in the case of R1_dried, thus confirming that a pre-treatment before extraction is able to remove a significant amount of moisture.…”
Section: Pyrolysis Processmentioning
confidence: 58%
“…A de‐hydration and decarboxylation process then occurs at 180–360 °C, and this is followed by the primary pyrolysis (300–380 °C) and the secondary pyrolysis at a higher temperature . Hydrogen production occurs at a high temperature (>600 °C), and it is therefore related to the fourth peak …”
Section: Resultsmentioning
confidence: 99%